Carbon-carbon composite material U-shaped part and preparation method thereof

By using the method of alternate laying of carbon fiber fabric and surface felt in the manufacture of carbon-carbon composite U-shaped parts, combined with special molds and multiple carbonization and impregnation processes, the problems of waste and insufficient strength of U-shaped parts in the prior art are solved, and high-density and high-strength product manufacturing is achieved.

CN119526785APending Publication Date: 2025-02-28HANGZHOU KAIKEN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411709525.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when manufacturing carbon-carbon composite U-shaped parts, thick plate blank processing is wasteful, the cost is high, and the fibers are not continuous, the strength is not high, and the service life is short.

Method used

The method of alternately laying carbon fiber fabric and carbon fiber surface felt is adopted to perform one-time molding through a special concave and convex mold, combined with step-type heating and carbonization and impregnation and density-enhancing processes, and then repeated twice, and finally pyrolyzed carbon coating is carried out.

Benefits of technology

The high density and high strength of carbon-carbon composite U-shaped parts are achieved, with product density ≥1.5g/cm3, tensile strength ≥130MPa, and bending strength ≥150Mpa, which reduces manufacturing costs and cycles and extends the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155309190000081
    Figure BDA0005155309190000081
  • Figure HDA0005155309200000011
    Figure HDA0005155309200000011
  • Figure HDA0005155309200000012
    Figure HDA0005155309200000012
Patent Text Reader

Abstract

The invention relates to the technical field of special-shaped part preparation, in particular to a carbon-carbon composite material U-shaped part and a preparation method thereof.The U-shaped part is prepared through a carbon cloth / surfacing mat alternate laying method, and layering is not prone to occurring after carbonization; a concave-convex die is used for manufacturing, and the product size is accurate. According to the technical scheme, operation is easy, equipment investment is small, and the manufacturing period is short; and large-batch and low-cost rapid production and manufacturing can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon-carbon composite materials, and in particular to a carbon-carbon composite U-shaped part and a preparation method thereof. Background Art

[0002] Carbon-carbon composite materials are widely used in aerospace, photovoltaic and other fields due to their excellent high temperature resistance, low thermal expansion coefficient, high strength and modulus at high temperature. At present, the manufacturing method of carbon-carbon composite plate and crucible products is relatively mature. Carbon fiber fabric is used to make preforms, which are then soaked in phenolic resin and preformed by a press. The carbon-carbon composite products are obtained by repeated impregnation-carbonization.

[0003] At present, for special-shaped thin-walled carbon-carbon products, such as U-shaped parts, thick plate blanks are mainly used for shaping and processing, which is wasteful and costly. In addition, the processed products have no fiber continuity, low strength, short service life, and are easy to damage. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a carbon-carbon composite U-shaped part and a preparation method thereof, which can effectively solve the above-mentioned problems of the prior art.

[0005] Technical Solution

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] The present invention provides a mold for preparing a U-shaped part of a carbon-carbon composite material, the mold comprising a concave mold and a convex mold, the convex mold is a T-shaped structure composed of a substrate and a bump, the concave mold is provided with a groove that matches the shape of the bump, and the width direction of the groove is greater than the width of the bump.

[0008] Furthermore, the concave mold is composed of a concave mold A and a concave mold B, and the concave mold A and the concave mold B are symmetrically arranged on both sides of the protrusion and are detachably connected to the base plate through fasteners.

[0009] Furthermore, the concave die A and the concave die B are not connected.

[0010] A method for preparing a carbon-carbon composite U-shaped part, which specifically includes the following preparation steps:

[0011] S1: Raw material preparation: Carbon fiber fabric and carbon fiber surface felt are selected as raw materials;

[0012] S2: Dipping: Evenly apply the glue on both sides of the carbon fiber fabric and the carbon fiber surface felt. The content of the glue after dipping is 30%-40%. Put the dipped materials into the oven for baking;

[0013] S3: Material laying: Cut the carbon fiber fabric and carbon fiber surface felt after the impregnation, and lay the carbon fiber fabric and carbon fiber surface felt alternately on the mold convex mold; after the material is laid, use the positioning pins and surrounding bolts on the mold to position and fasten the concave and convex molds together, and tighten the mold bolts alternately. After the mold is closed, the gap between the upper and lower molds is ≤0.1mm;

[0014] S4: Curing: Put the mold after closing into the oven for curing. After curing, when the mold temperature drops below 50°C, open the mold and take out the product.

[0015] S5: Carbonization and impregnation: The demoulded product is taken out and placed in a carbonization furnace for step-by-step temperature carbonization; the carbonized product is taken out and placed in an impregnation furnace for impregnation and densification; and then the impregnated product is carbonized; wherein the impregnation-carbonization process is repeated 1-3 times;

[0016] S6: Machining: The impregnation-carbonized product is machined according to the drawing to obtain a U-shaped product of corresponding size; the wall thickness of the product is formed in one step, and the wall thickness does not need to be processed, which greatly saves processing time and reduces manufacturing costs and cycles; the U-shaped parts manufactured by traditional solutions need to be processed for wall thickness, which is complicated and requires customized processing tools;

[0017] S7: Pyrolytic carbon coating: The processed product is placed in a CVD furnace for pyrolytic carbon coating.

[0018] Furthermore, in step S1, the carbon fiber fabric is T300 or T700 / 12k / plain carbon fiber fabric with a gram weight of 400-500gsm; the carbon fiber surface felt is T300 or T700 grade carbon fiber surface felt with a gram weight of 10-30gsm, and the surface felt fiber length is 30-70mm.

[0019] Further, in step S2, the baking temperature is 50-70°C, and the baking time is 20-30min; the glue liquid adopts a mixture of boron-modified phenolic resin and 800-mesh silicon powder, and the mixing weight ratio is 100:1-2, the mixed glue liquid temperature is 30-40°C, the stirring time is 20-30min, the stirring speed is 100-200 rpm, and the viscosity of the glue liquid after mixing is ≤500mpa.s; compared with ordinary phenolic resin, the boron-modified resin greatly improves the residual carbon rate of the resin. Preferably, the glue liquid adopts a mixture of boron-modified phenolic resin and 800-mesh silicon powder, and the mixing weight ratio is 100:1.

[0020] Furthermore, in step S3, 4-8 pieces of carbon fiber fabric and 4-8 pieces of carbon fiber surface felt are cut, and the carbon fiber fabric and carbon fiber surface felt are alternately laid on the mold convex mold; the alternating laying form of carbon fiber fabric and carbon fiber surface felt greatly enhances the interlayer bonding strength of the product.

[0021] In step S3, specifically, referring to the product size of the U-shaped part, a U-shaped part mold is designed. The mold is a concave and convex mold form, and bolts and nuts are used to close the mold around. To facilitate product demolding, the concave mold is assembled and consists of a concave mold A and a concave mold B to avoid product scrapping due to product sticking to the mold. If the product batch is large, the upper and lower molds can be fixed to the upper and lower pallets of the press respectively, and the press program can be set to automatically close and open the mold to realize automated batch production, save labor costs, and shorten the manufacturing cycle. After the material is laid, the concave and convex molds are positioned and fastened together with the help of the positioning pins on the mold and the bolts around it, and the clamping bolts are tightened alternately. After closing the mold, the gap between the upper and lower molds is ≤0.1mm.

[0022] Further, in step S4, the curing system is: 100℃ / (1-2)h+180℃ / (1-2)h. After the curing is completed, the mold temperature drops below 50℃, the mold is opened, and the product is taken out. The product density is 1.4-1.6g / cm 3 ; Using the press to automate batch production, each mold is 3 hours, which can meet the needs of batch production and greatly reduce manufacturing costs. Compared with the traditional manufacturing process, the initial density is higher and the subsequent densification effect is more obvious. The traditional process uses ordinary resin glue, and the product density after curing is 1.3-1.4g / cm 3 In step S4, the mold can be placed in an oven for curing, or it can be used with a press to achieve automated production. The operating program is input into the press to achieve automatic mold closing-curing-opening operations. The press is used for automated batch production, with a cycle of 3 hours per mold.

[0023] Furthermore, in step S5, the temperature is raised stepwise for carbonization, the first carbonization procedure is 900°C / (4-6)h, the carbonization procedure after the first immersion is 1600°C / (3-5)h, and the carbonization procedure after the second immersion is 2000°C / (4-6)h, so as to gradually increase the product use temperature and reduce product deformation;

[0024] In step S5, the impregnation resin is a high-residue furfural resin, the resin viscosity is 100-300mpas, the impregnation pressure is 2-5MPa, and the curing temperature after impregnation is 150°C / 1h+200°C / 4h; the impregnation-carbonization cycle is repeated twice.

[0025] Furthermore, in step S7, the deposition temperature is 1000-1200°C, the natural gas flow rate is 100-150 SLM, and the deposition time is 50-80 hours. A dense carbon coating is deposited on the surface of the product, which improves the oxidation resistance of the product and greatly extends the service life of the product.

[0026] The U-shaped part prepared by the present invention has a product density of ≥1.5g / cm 3 , tensile strength ≥130MPa, flexural strength ≥150Mpa.

[0027] A thin-walled carbon-carbon composite material U-shaped part can be prepared by using the mold or the carbon-carbon composite material U-shaped part preparation method; and the thickness of the U-shaped part is 1-3 mm.

[0028] Beneficial Effects

[0029] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0030] (1) The present invention provides a method for preparing a thin-walled (1-3 mm) carbon-carbon composite U-shaped part, which has a simple manufacturing process and is combined with a heat-releasing carbon coating to increase the service life of the product.

[0031] (2) The U-shaped parts are prepared by alternating layers of carbon cloth / surface felt, which are not easy to delaminate after carbonization; and the concave and convex molds are used for manufacturing, so the product size is precise.

[0032] (3) The technical solution of the present invention is simple to operate, requires little equipment investment, and has a short manufacturing cycle; it can meet the needs of large-scale, low-cost rapid production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 It is a schematic diagram of the punch structure;

[0035] Figure 2 It is a schematic diagram of the die structure.

[0036] The numbers in the figure represent:

[0037] 1- male mold; 11- substrate; 12- bump; 2- female mold; 21- female mold A; 22- female mold B. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The present invention will be further described below in conjunction with the embodiments.

[0040] The manufacturers and brands of the raw materials in the embodiments and comparative examples are as follows:

[0041] Carbon fiber fabric: Made of Toray T700;

[0042] Carbon fiber surface felt: Made of Toray T300;

[0043] Boron modified resin: Shengquan PF9506;

[0044] 800 mesh silica fume: The manufacturer has no special requirements, and the mesh of silica fume can be 800 mesh;

[0045] Ordinary phenolic resin: no special requirements;

[0046] High residual carbon furfural resin: Shengquan FAR PLUS .

[0047] (I) Embodiment

[0048] Embodiment 1:

[0049] A method for preparing a carbon-carbon composite U-shaped part, which specifically includes the following preparation steps:

[0050] S1: Raw material preparation: carbon fiber fabric and carbon fiber surface felt are selected as raw materials; wherein the carbon fiber fabric is Toray T700; the carbon fiber surface felt is Toray T300.

[0051] S2: Dipping: The glue is evenly applied on both sides of the carbon fiber fabric and the carbon fiber surface felt. The content of the glue after dipping is 35%. The dipping material is placed in an oven for baking at a temperature of 60°C for 30 minutes. The glue is a mixture of boron-modified phenolic resin and 800-mesh silicon powder at a weight ratio of 100:1. The temperature of the mixed glue is 35°C, the stirring time is 20 minutes, the stirring speed is 150 rpm, and the viscosity of the mixed glue is ≤500mpa.s.

[0052] S3: Material laying: Cut the impregnated carbon fiber fabric and carbon fiber surface felt into sizes of 1200*210mm, and lay 6 pieces of carbon fiber fabric and 5 pieces of carbon fiber surface felt alternately on the punch of the mold; after the materials are laid, use the positioning pins and surrounding bolts on the mold to position and fasten the concave and convex molds together, and tighten the mold bolts alternately. After the mold is closed, the gap between the upper and lower molds is ≤0.1mm;

[0053] S4: Curing: Put the mold into the oven for curing. The curing system is 100℃ / (1.5)h+180℃ / (1.5)h. After curing, when the mold temperature drops below 50℃, open the mold and take out the product.

[0054] S5: Carbonization and impregnation: The demoulded product is taken out and placed in a carbonization furnace for step-by-step temperature carbonization; the carbonized product is taken out and placed in an impregnation furnace for impregnation and densification; and then the impregnated product is carbonized; the impregnation-carbonization process is repeated twice;

[0055] Among them, in the carbonization process, the first carbonization process: 900℃ / (5)h, the carbonization process after the first immersion: 1600℃ / (4)h, the carbonization process after the second immersion: 2000℃ / (5)h, gradually increasing the product use temperature and reducing product deformation;

[0056] In the impregnation process, the impregnation resin is high carbon residual furfural resin, the impregnation pressure is 3.5MPa, and the curing temperature after impregnation is 150℃ / 1h+200℃ / 4h;

[0057] S6: Machining: The impregnation-carbonized product is machined according to the drawing to obtain a U-shaped product of corresponding size; the wall thickness of the product is formed in one step, and the wall thickness does not need to be processed, which greatly saves processing time and reduces manufacturing costs and cycles; the U-shaped parts manufactured by traditional solutions need to be processed for wall thickness, which is complicated and requires customized processing tools;

[0058] S7: Pyrolytic carbon coating: Place the processed product into a CVD furnace for pyrolytic carbon coating, with a deposition temperature of 1100°C, a natural gas flow rate of 120 SLM, and a deposition time of 65 h.

[0059] Comparative Example 1:

[0060] The only difference from Example 1 is that the glue in step S2 uses ordinary phenolic resin.

[0061] Comparative Example 2:

[0062] The only difference from Example 1 is that the raw material is only carbon fiber fabric, and the carbon fiber fabric is alternately laid on the mold convex mold.

[0063] Comparative Example 3:

[0064] The only difference from Example 1 is that the raw material is only carbon fiber surface felt, and the carbon fiber surface felt is alternately laid on the mold convex mold.

[0065] Comparative Example 4:

[0066] The only difference from Example 1 is that no 800 mesh silicon powder is added.

[0067] Comparative Example 5:

[0068] The only difference from Example 1 is that step S7 of pyrolyzing the carbon coating is missing.

[0069] (II) Performance test

[0070] (1) Test method

[0071] Bending properties: Part 2 of Test Methods for Carbon-Carbon Composite Carbon Materials;

[0072] (2) Test results

[0073]

[0074] The U-shaped part prepared by the technical solution of the present invention has good performance and short manufacturing cycle. Its product density is ≥1.5g / cm 3 , bending strength ≥150Mpa. The U-shaped parts are prepared by the method of alternately laying carbon cloth / surface felt, which is not easy to delaminate after carbonization; the concave and convex molds are used for manufacturing, and the product size is accurate. The technical solution of the present invention is simple to operate, requires little equipment investment, and has a short manufacturing cycle; it can meet the needs of large-scale, low-cost rapid production and manufacturing.

[0075] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A mold for preparing a carbon-carbon composite U-shaped part, characterized in that: The mold includes a concave mold and a convex mold. The convex mold is a T-shaped structure composed of a substrate and a bump. A groove matching the shape of the bump is provided in the concave mold, and the width dimension of the groove is greater than the width of the bump.

2. A mold for preparing a carbon-carbon composite U-shaped part according to claim 1, characterized in that: The concave die is composed of a concave die A and a concave die B, and the concave die A and the concave die B are symmetrically arranged on both sides of the protrusion and are detachably connected to the base plate through fasteners.

3. A mold for preparing a carbon-carbon composite U-shaped part according to claim 2, characterized in that: The die A and die B are not connected.

4. A method for preparing a carbon-carbon composite U-shaped part, characterized in that: The method is prepared by using a mold as described in any one of claims 1 to 3, and specifically comprises the following preparation steps: S1: Raw material preparation: Carbon fiber fabric and carbon fiber surface felt are selected as raw materials; S2: Dipping: Apply the glue evenly on both sides of the carbon fiber fabric and the carbon fiber surface felt. The content of the glue after dipping is 30%-40%. Put the dipped materials into the oven for baking. S3: Material laying: Cut the carbon fiber fabric and carbon fiber surface felt after the impregnation, and lay the carbon fiber fabric and carbon fiber surface felt alternately on the mold convex mold; after the material is laid, use the positioning pins and surrounding bolts on the mold to position and fasten the concave and convex molds together, and tighten the mold bolts alternately. After the mold is closed, the gap between the upper and lower molds is ≤0.1mm; S4: Curing: Put the mold after closing into the oven for curing. After curing, when the mold temperature drops below 50°C, open the mold and take out the product. S5: Carbonization and impregnation: The demoulded product is taken out and placed in a carbonization furnace for step-by-step temperature carbonization; the carbonized product is taken out and placed in an impregnation furnace for impregnation and densification; and then the impregnated product is carbonized; wherein the impregnation-carbonization process is repeated 1-3 times; S6: Machining: The impregnation-carbonization product is machined according to the size of the drawing to obtain a U-shaped product of corresponding size; S7: Pyrolytic carbon coating: The processed product is placed in a CVD furnace for pyrolytic carbon coating.

5. The method for preparing a carbon-carbon composite U-shaped part according to claim 4, characterized in that: In step S1, the carbon fiber fabric is T300 or T700 / 12k / plain carbon fiber fabric with a gram weight of 400-500gsm; the carbon fiber surface felt is T300 or T700 grade carbon fiber surface felt with a gram weight of 10-30gsm, and the surface felt fiber length is 30-70mm.

6. The method for preparing a carbon-carbon composite U-shaped part according to claim 4, characterized in that: In step S2, the baking temperature is 50-70°C, and the baking time is 20-30min; the glue liquid adopts a mixture of boron-modified phenolic resin and 800-mesh silicon powder, and the mixing weight ratio is 100:1-2, the mixed glue liquid temperature is 30-40°C, the stirring time is 20-30min, the stirring speed is 100-200 rpm, and the viscosity of the glue liquid after mixing is ≤500mpa.s.

7. The method for preparing a carbon-carbon composite U-shaped part according to claim 4, characterized in that: In step S3, 4 to 8 pieces of carbon fiber fabric and 4 to 8 pieces of carbon fiber surface felt are cut, and the carbon fiber fabric and the carbon fiber surface felt are alternately laid on the mold convex mold.

8. The method for preparing a carbon-carbon composite U-shaped part according to claim 4, characterized in that: In step S4, the curing system is: 100°C / (1-2)h+180°C / (1-2)h. After the curing is completed, when the mold temperature drops below 50°C, the mold is opened and the product is taken out.

9. The method for preparing a carbon-carbon composite U-shaped part according to claim 4, characterized in that: In step S5, the temperature is raised stepwise for carbonization, the first carbonization process is 900°C / (4-6)h, the carbonization process after the first impregnation is 1600°C / (3-5)h, and the carbonization process after the second impregnation is 2000°C / (4-6)h; the impregnation-carbonization cycle is repeated twice; In step S5, in the impregnation process, the impregnation resin is a high carbon residue furfural resin, the resin viscosity is 100-300mpas, the impregnation pressure is 2-5MPa, and the curing temperature after impregnation is 150°C / 1h+200°C / 4h; the impregnation-carbonization cycle is repeated twice; In step S7, the deposition temperature is 1000-1200°C, the natural gas flow rate is 100-150 SLM, and the deposition time is 50-80 hours.

10. A thin-walled carbon-carbon composite U-shaped part, which can be prepared by using the mold described in any one of claims 1 to 3 or the method for preparing a carbon-carbon composite U-shaped part described in any one of claims 4 to 9; and the thickness of the U-shaped part is 1-3 mm.